Utilizing evidence-based lessons learned for enhanced organizational innovation and change - McIntyre, Susan G., 1956-; Dalkir, Kimiz; Paul, Perry; Kitimbo, Irene C.; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2015)
"This book links the theoretical foundation of the "lessons learned" approach with current tools and evidence-based research in support of organizational development, outlining best practices and emerging research in organizational learning"--Provided by publisher.
Lessons learned: theory and practice / Irene Kitimbo -- Learning lessons for organizational learning, process improvement, and innovation / Susan G. McIntyre -- Essential stages of the lessons learned process / Perry Paul -- Operationalization of the lessons learned process: a practical approach / Peter Avis, Joe Sharpe -- Proactive review / Ditte Kolbaek -- A model for evidence-based learning through lesson-learning systems: examples from the oil and gas sector / Nicholas John Milton -- A lessons learned assessment approach: the role of technology through user requirements / Pierrette Champoux -- A lessons framework for civil-military-police conflict and disaster management: an Australian perspective / Mellisa Bowers, Gwen Cherne -- Moving the ball down the field: improving the USAF's Pacific Air Forces / Mark Reid, Dan Ashcraft -- Using stories to institutionalize lessons learned: how to better remember and learn from the past / Kimiz Dalkir -- A proposed analytical framework for Canadian whole-of-government lessons learned / Susan G. McIntyre -- Common pitfalls and shortcomings of lessons learned programs: evidence from an online survey / Ian Fry -- Senior leadership and lessons learned in the Australian Defence Organisation / Sasa Baskarada, Jamie Watson, Jason Cromarty -- The role of organizational culture in the success of changing behaviour / Ian Nicholls, Perry Paul -- Conclusion and future directions / Kimiz Dalkir, Susan G. McIntyre.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 11/05/2014).
Keywords: Organizational change; Organizational learning; Continuous improvement; Organizational behavior; Organizational change; Organizational culture; Project management; Technological integration; Electronic books